(untitled) (Altre Modernità, 2020)
In the second half of the nineteenth century appears the figure of the "chiffonnier", daughter of the modern metropolis, where, according to Benjamin, the fragments of the consumer society are deposited and preserved every day. Baudelaire gives the first definition of the "ragtag" in a famous passage of the essay Du vin et du haschisch of 1851, useful for the analysis of two Perecquien projects, L’Herbier des villes and Lieux, which present themselves as real archives. Perec collected the derisory traces of urban life, to which we generally do not give any importance, cinema, subway, museum tickets, posters, flyers, receipts that constitute "signes d’ancrage" or "objets témoins" in constant dialogue with the writing. Especially since the 1960s, the art world, by eliminating every distance that separates it from everyday life, reintegrates the junk object. Perec’s work thus fits into a wider artistic revolution, which manifests a different attention to the value of everyday objects. Starting from the theoretical observations of Foucault, Derrida, Benjamin and Baldacci, the contribution proposes a reflection on the memorial practices and on the forms of knowledge that distinguish the two Perecquien projects, which have remained unfinished.